1988
DOI: 10.1128/jvi.62.9.3175-3181.1988
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the role of the 2'-5'-oligoadenylate synthetase-RNase L pathway in beta interferon-mediated inhibition of encephalomyocarditis virus replication

Abstract: Interferons inhibit the replication of vesicular stomatitis virus (VSV), but not of encephalomyocarditis virus (EMCV), in mouse JLSV-11 cells. We report the isolation of clonal derivatives from this cell line in which the replication of both viruses is impaired by interferons. These clones were selected from the parental line by virtue of their rescue by interferon treatment from the cytopathic effects of EMCV infection. In one such clone, RK8, the replication of VSV and EMCV and the production of resident mur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…LS1 cells did not extend the range of viruses sensitive to 2-5A pathway antiviral activity to include VSV, confirming previous studies which demonstrated that multiple mechanisms are responsible for the full range of IFN's antiviral effects (31,36).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…LS1 cells did not extend the range of viruses sensitive to 2-5A pathway antiviral activity to include VSV, confirming previous studies which demonstrated that multiple mechanisms are responsible for the full range of IFN's antiviral effects (31,36).…”
Section: Discussionsupporting
confidence: 86%
“…Introduction of 2-5A into cells has been shown to reduce the cytopathic effects of several viruses, including vesicular stomatitis virus (VSV), EMCV, poliovirus, and Semliki Forest virus (1), whereas a 2-5A analog inhibitor of RNase L has reduced the anti-EMCV activity of IFN in intact cells (51). Further, in cell lines in which 2-5A pathway activity is defective, EMCV replication is resistant to the inhibitory effects of IFN (31). The cloning of cDNAs encoding 2-5A synthetase (35,43) and RNase L (56) has provided a means of definitively addressing the antiviral function of the 2-5A system in cells.…”
mentioning
confidence: 99%
“…In addition, 2-5A-dependent RNase levels have been reported to be elevated during cell differentiation (33). Because several investigations have implicated the 2-5A system in the mechanism by which interferon inhibits the replication of picornaviruses (9,35,56), it is conceivable that the 2-5A system contributes to the restricted LCMV replication in NGF-treated PC12 cells. Nonetheless, after exposure to gamma interferon (100 U/ml for 24 h), BHK-21 cells had levels of 2-5A synthetase higher than that found in NGF-treated PC12 cells but only a very modest (5to 10-fold) concomitant decrease in LCMV production (data not shown), suggesting that it is very unlikely the 2-5A system is responsible for the 1,000-fold reduction in LCMV yield found in NGF-treated PC12 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Slattery et al (45) established that removal of 2-5A from RNase L restored its latency. The 2-5A RNase L system is a mediator of the inhibition of encephalomyocarditis virus replication by IFN (54).…”
Section: Exploring the Interferon Systemmentioning
confidence: 99%